(* \$Id: ex.thy,v 1.2 2004/11/23 15:14:34 webertj Exp \$ *) header {* Replace, Reverse and Delete *} (*<*) theory ex imports Main begin (*>*) text{* Define a function @{term replace}, such that @{term"replace x y zs"} yields @{term zs} with every occurrence of @{term x} replaced by @{term y}. *} consts replace :: "'a \ 'a \ 'a list \ 'a list" text {* Prove or disprove (by counterexample) the following theorems. You may have to prove some lemmas first. *} theorem "rev(replace x y zs) = replace x y (rev zs)" (*<*)oops(*>*) theorem "replace x y (replace u v zs) = replace u v (replace x y zs)" (*<*)oops(*>*) theorem "replace y z (replace x y zs) = replace x z zs" (*<*)oops(*>*) text{* Define two functions for removing elements from a list: @{term"del1 x xs"} deletes the first occurrence (from the left) of @{term x} in @{term xs}, @{term"delall x xs"} all of them. *} consts del1 :: "'a \ 'a list \ 'a list" delall :: "'a \ 'a list \ 'a list" text {* Prove or disprove (by counterexample) the following theorems. *} theorem "del1 x (delall x xs) = delall x xs" (*<*)oops(*>*) theorem "delall x (delall x xs) = delall x xs" (*<*)oops(*>*) theorem "delall x (del1 x xs) = delall x xs" (*<*)oops(*>*) theorem "del1 x (del1 y zs) = del1 y (del1 x zs)" (*<*)oops(*>*) theorem "delall x (del1 y zs) = del1 y (delall x zs)" (*<*)oops(*>*) theorem "delall x (delall y zs) = delall y (delall x zs)" (*<*)oops(*>*) theorem "del1 y (replace x y xs) = del1 x xs" (*<*)oops(*>*) theorem "delall y (replace x y xs) = delall x xs" (*<*)oops(*>*) theorem "replace x y (delall x zs) = delall x zs" (*<*)oops(*>*) theorem "replace x y (delall z zs) = delall z (replace x y zs)" (*<*)oops(*>*) theorem "rev(del1 x xs) = del1 x (rev xs)" (*<*)oops(*>*) theorem "rev(delall x xs) = delall x (rev xs)" (*<*)oops(*>*) (*<*) end (*>*)